2022
DOI: 10.1038/s41598-022-25864-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety of transcutaneous auricular vagus nerve stimulation (taVNS): a systematic review and meta-analysis

Abstract: Transcutaneous auricular vagus nerve stimulation (taVNS) has been investigated as a novel neuromodulation tool. Although taVNS is generally considered safe with only mild and transient adverse effects (AEs), those specifically caused by taVNS have not yet been investigated. This systematic review and meta-analysis on taVNS aimed to (1) systematically analyze study characteristics and AE assessment, (2) characterize and analyze possible AEs and their incidence, (3) search for predictable risk factors, (4) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 45 publications
(75 reference statements)
1
22
0
Order By: Relevance
“…Our recent meta-analysis of 167 studies assessing 5,827 subjects showed that this technique is a safe and feasible option for intervention, with a low incidence of adverse events and no severe adverse events reported associated with the stimulation. 12…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our recent meta-analysis of 167 studies assessing 5,827 subjects showed that this technique is a safe and feasible option for intervention, with a low incidence of adverse events and no severe adverse events reported associated with the stimulation. 12…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32] However, aVNS has been demonstrated to be a more feasible, accessible, and a safer therapy. 12…”
Section: Expression Of Cd31/alk5 In Capillary Endothelial Cell In Per...mentioning
confidence: 99%
See 2 more Smart Citations
“…The brain chemistry, nociceptive processing, inflammation, and autonomic function are modulated by neurostimulation for different therapeutic purposes ( Li et al, 2015 ; Babygirija et al, 2017 ; Kaniusas et al, 2019a ). Even though neuromodulation therapy is generally considered safe with only mild and transient adverse effects ( Redgrave et al, 2018 ; Kim et al, 2022 ), the mechanistic understanding of neuromodulation is still incomplete ( Yap et al, 2020 ). While methodological standardization of the therapy is in progress ( Farmer et al, 2021 ), personalization of neuromodulation is still insufficient ( Yu et al, 2022 ; Kaniusas et al, 2019b ) for a successful translation of neuromodulation into mainstream clinical practice ( Goggins et al, 2022 ).…”
mentioning
confidence: 99%